2011
DOI: 10.1007/s00262-011-1117-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects of Taxol and Adryamicin in breast cancer patients

Abstract: Antineoplastic chemotherapy still consists in the major first-line therapeutics against cancer. Several reports have described the immunomodulatory effects of these drugs based on in vitro treatment, but no previous data are known about these effects in patients and its association with immunological-mediated toxicity. In this study, we first characterize the immunological profile of advanced breast cancer patients treated with doxorubicin and paclitaxel protocols, immediately after chemotherapy infusion. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…The results of multivariable analysis revealed that the risk of a poor prognosis is likely to be more dependent on MDSCs levels >1%, which were associated with a higher probability of mortality when adjusted for other potential prognostic factors. Certain anti-cancer chemotherapeutic agents, including gemcitabine, have been reported to alter MDSC levels, resulting in improvement of cellular immunocompetence (17,25). MDSC levels in the peripheral blood and in the pleural effusion of patients with metastatic breast cancer have been previously demonstrated to decrease following chemotherapy with gemcitabine (26).…”
Section: Discussionmentioning
confidence: 99%
“…The results of multivariable analysis revealed that the risk of a poor prognosis is likely to be more dependent on MDSCs levels >1%, which were associated with a higher probability of mortality when adjusted for other potential prognostic factors. Certain anti-cancer chemotherapeutic agents, including gemcitabine, have been reported to alter MDSC levels, resulting in improvement of cellular immunocompetence (17,25). MDSC levels in the peripheral blood and in the pleural effusion of patients with metastatic breast cancer have been previously demonstrated to decrease following chemotherapy with gemcitabine (26).…”
Section: Discussionmentioning
confidence: 99%
“…The hostile tumor micro-environment and its chemical composition must indeed shape the immune infiltrate, and MDR1 expression by anti-tumor immune cells may favor their preservation despite harsh environmental conditions. The immune infiltrate is also modulated by MDR1-associated anti-neoplastic agents, 90,101 and evaluation of MDR1 level on immune cells could be an indicator of these treatments’ effects.…”
Section: Introductionmentioning
confidence: 99%
“…19 These data are in agreement with the literature, since the main adverse effects observed in treatment with commercial PTX are the following: adverse reactions relating to the bone marrow (alterations in leucocytes, thrombocytopenia, anemia induced by direct damage to erythrocytes), infections, hypersensitivity to hemorrhage, and neurotoxicity. 35,40,41 In relation to biochemical parameters, no relationship between PTX dose and alterations in hepatic function was demonstrated in patients without base hepatic alterations. Published research showed only rare relationships to hepatic necrosis and hepatic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%